Cover Feature: Phototunable Lignin Plastics to Enable Recyclability (ChemSusChem 19/2021). Issue 19 (15th September 2021) - Hu, Cheng; Zhao, Mingzhen; Li, Qiang; Liu, Zhihua; Hao, Naijia; Meng, Xianzhi; Li, Jinghao; Lin, Furong; Li, Chenxuan; Fang, Lei; Dai, Susie Y.; Ragauskas, Arthur J.; et al.
Abstract : The Cover Feature shows that a PMMA‐g‐lignin‐ZnO polymeric film with superior mechanical performance has been developed, where photo‐degradable lignin serves as core to be cleaved by ZnO nano‐catalysts and to enable the recycling of PMMA after UV irradiation. More information can be found in the Full Paper by C. Hu, M. Zhao, et al .